“ESG score” vs. “ESG rating”: a conceptual model for the sustainability assessment and self-assessment of European SMEs - Murè, Pina; Giorgio, Saverio; Antonelli, Valeria; Crisafulli, Antonino (Frontiers in Environmental Economics, 2024)
This paper aims to contribute to the ongoing discourse regarding the distinctions and application of scoring and rating systems by presenting a conceptual model designed to assess and self-assess small and medium-sized enterprises (hereinafter also “SMEs”) on their sustainability transition. Indeed, SMEs operate in very different economic contexts and have simplified organizational and governance structures. These characteristics can be effectively captured through this conceptual model based on a customized questionnaire tailored to the specificities of SMEs. Following an analysis of existing literature and regulatory frameworks, a conceptual model is proposed that includes a questionnaire that, unlike commonly proposed industry questionnaires, is designed to generate an Environmental, Social and Governance (hereinafter also “ESG”) Score complemented by a forward-looking perspective. This model can be useful for SMEs, as it allows them to self-assess their strengths and weaknesses in the sustainability transition process, highlighting specific needs and suggesting actions to improve their sustainability transition. It also allows banks to make a more accurate assessment of the sustainability of their customers, facilitating the redefinition of green and social credit products according to the needs of SMEs. Additionally, it also supports supply chain leaders in ensuring a sustainable supply chain by facilitating the sustainability assessment of SMEs. This is so that everything complies with the new European Union (hereinafter also “EU”) regulations. Finally, the questionnaire is currently being tested at a local bank and has been proposed to SME suppliers in a specific supply chain. It will be possible to make changes to the questionnaire based on the feedback received during the administration phase.